EXPLORING DIFFERENTIATED PROJECT-BASED LEARNING ASSESSMENT PRACTICES TO STRENGTHEN NUMERACY LITERACY IN ELEMENTARY SCHOOLS - Siswanto Dwi Antoro; Ivayuni Listiani; Muh. Waskito Ardi; Endang Sri Maruti (JURNAL EDUSCIENCE, 2026)
Purpose – This study investigates differentiated project-based assessment practices as a strategic approach to strengthening literacy and numeracy in elementary schools within the spirit of Merdeka Belajar (Freedom to Learn). Emerging from the gap between the paradigm of assessment as learning and conventional, outcome-oriented practices, this study examines how teachers design, implement, and reflect on student-centered assessments grounded in authentic life contexts.Methodology – A multi-case qualitative approach was employed across three elementary schools in East Java: SDN Manukan Kulon (Surabaya), SDN Kedung 1 (Probolinggo), and SDN Kanten 1 (Bojonegoro), with data collected through in-depth interviews, participatory observations, and analysis of assessment documents.Findings – The findings reveal four consistent cross-contextual patterns: contextualized assessment planning, differentiated implementation of processes and products, the use of authentic instruments that evaluate thinking processes, and teachers' professional reflection that strengthens pedagogical awareness. The integration of these four dimensions yielded the Differentiated Project-Based Assessment Framework (DiPBAF), a synthesized model that represents a reflective and equitable learning cycle. This model underscores an epistemological shift in assessment—from a mere measurement tool to a transformative learning vehicle that fosters autonomy, empathy, and collaboration.Contribution – Theoretically, this research enriches the discourse on 21st-century assessment oriented toward process and reflection; practically, it offers new directions for contextual assessment policies that promote teacher professionalism and high-quality human-centered learning.